2021
DOI: 10.1080/13621718.2021.2014742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ni interlayer on microstructure and mechanical properties of Al/Mg dissimilar friction stir welding joints

Abstract: In this work, friction stir welding (FSW) was carried out for the flat butt welding tests of Al/Mg dissimilar alloys by introducing Ni foil interlayer with different thickness. The effect of the thickness of interlayer on microstructure and mechanical properties of the FSW joints was explored. The results revealed that with the increase of the thickness of Ni, the effective bearing area of the weld nugget zone (WNZ) increased. It achieved the maximum value when the thickness of interlayer was 0.3 mm, and a den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 30 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…The conventional Al/Mg FSW has the production of flocculent Al 12 Mg 17 and layered Al 3 Mg 2 IMCs. 15 Through EDS energy spectrum analysis, a large amount of Al 12 Mg 17 and Al 3 Mg 2 IMCs were reduced in the Cu interlayer Al/Mg joints, and they were transformed into granular and flocculent distribution in morphology (Figure 2(e) and (f)). The IMCs consisting of Al 2 Cu, CuMg 2 , and Al 2 CuMg were generated in the WNZ (Figure 2(g) and (i)), indicating that adding Cu interlayer inhibited the production of aluminium–magnesium IMCs.…”
Section: Resultsmentioning
confidence: 99%
“…The conventional Al/Mg FSW has the production of flocculent Al 12 Mg 17 and layered Al 3 Mg 2 IMCs. 15 Through EDS energy spectrum analysis, a large amount of Al 12 Mg 17 and Al 3 Mg 2 IMCs were reduced in the Cu interlayer Al/Mg joints, and they were transformed into granular and flocculent distribution in morphology (Figure 2(e) and (f)). The IMCs consisting of Al 2 Cu, CuMg 2 , and Al 2 CuMg were generated in the WNZ (Figure 2(g) and (i)), indicating that adding Cu interlayer inhibited the production of aluminium–magnesium IMCs.…”
Section: Resultsmentioning
confidence: 99%
“…The first involves the use of modified techniques, such as welding tool pin offset [6], ultrasonic vibration assistance [7], and forced cooling [8], to regulate heat generation and distribution. The second approach involves the application of metallurgical methods, including the addition of interlayers such as Ni [9], Zr [10], and Zn [7,11,12], to control the metallurgical reactions leading to IMC formation. Previous studies have demonstrated the effectiveness of these methods in controlling IMC formation and improving the mechanical properties of Al/Mg dissimilar joints.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the effectiveness of these methods in controlling IMC formation and improving the mechanical properties of Al/Mg dissimilar joints. However, it is important to note that the direct contact and mixing of Al/Mg alloys within the nugget zone during friction stir welding are unavoidable, consequently resulting in the formation of Al-Mg series IMCs [9].…”
Section: Introductionmentioning
confidence: 99%